Perceptions Assessment of a Group of Puerto Rican Pregnant Adolescents Regarding the Susceptibility, Severity, Benefits and Barriers of Teenage Pregnancy - Sandoval, Juanita; Santos-Ortiz, María del Carmen; Lebrón-de Avilés, Carmen; Dávila-Torres, René R. (Puerto Rico Health Sciences Journal, 2013)
See manuscript